2013
DOI: 10.1155/2013/134589
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod-Dependent Effects of 4-tert-Octylphenol on Adherens and Gap Junction Proteins in Bank Vole Seminiferous Tubules

Abstract: In the present study we evaluated in vivo and in vitro effects of 4-tert-octylphenol (OP) on the expression and distribution of adherens and gap junction proteins, N-cadherin, β-catenin, and connexin 43 (Cx43), in testes of seasonally breeding rodents, bank voles. We found that in bank vole testes expression and distribution of N-cadherin, β-catenin, and Cx43 were photoperiod dependent. Long-term treatment with OP (200 mg/kg b.w.) resulted in the reduction of junction proteins expressions (P < 0.05, P < 0.01) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Consistently, membranous and cytoplasmic b-catenin distribution in rat seminiferous epithelium was reported previously (Mulholland et al, 2001;Johnson & Boekelheide, 2002;Lee et al, 2003). Studies performed in this laboratory demonstrated that such localization of b-catenin in adult testes is also typical for other mammalian species, namely pig and bank vole (Hejmej et al, 2012(Hejmej et al, , 2013. DeBellefeuille et al (2003) have shown that catenins (a and b) interact with E-cadherin and form part of the AJs in rat epididymis.…”
Section: (A) (B)supporting
confidence: 84%
“…Consistently, membranous and cytoplasmic b-catenin distribution in rat seminiferous epithelium was reported previously (Mulholland et al, 2001;Johnson & Boekelheide, 2002;Lee et al, 2003). Studies performed in this laboratory demonstrated that such localization of b-catenin in adult testes is also typical for other mammalian species, namely pig and bank vole (Hejmej et al, 2012(Hejmej et al, , 2013. DeBellefeuille et al (2003) have shown that catenins (a and b) interact with E-cadherin and form part of the AJs in rat epididymis.…”
Section: (A) (B)supporting
confidence: 84%
“…Our earlier studies have revealed hormonal imbalances in horse cryptorchid testes, i.e., reduced testosterone synthesis and increased androgen aromatization [51]. Additionally, specific changes in testicular cell hormonal controls due to endogenous (or exogenous) factors also affect cell-to-cell and molecule-to-molecule interactions [52][53][54][55] that in turn affect the morphofunctional testis status.…”
Section: Discussionmentioning
confidence: 99%